Evaluación de la protección estatal a las familias de los reclusos del centro penitenciario el bosque, con domicilio en el barrio la paz de Barranquilla en el año 2009 (2010)
The family is the fundamental society´s nucleus, and therefore it should be source of rights and of duties that should be protected by the State, and in turn it should be corresponsable of the rights that the society grants him. The main objective of this project is to determine the participation of the State in the support to the families of the prisoner’s family head that are in the jail the Forest of the Barranquilla city. This investigation the deductive method the one was used which leaves from the general thing to the particular thing; a statistical work was also made in which important information was obtained about the families that have people confined in the jail the forest. After having carried out this work it is appreciated the condition of forgetfulness clearly in which you/they are hundred of families that at the moment are main characters of this social reality. One cannot conceive that in a Social State of Right he/she forgets the importance of the main institution of the same one, the family.